Treatment of distal ulcerative colitis (proctosigmoiditis) in relapse: comparison of hydrocortisone enemas and rectal hydrocortisone foam. Issue 10 (October 1980) - Ruddell, W S; Dickinson, R J; Dixon, M F; Axon, A T
Abstract : Thirty patients with distal colitis (proctosigmoiditis) in relapse were randonly allocated to twice daily treatment with traditional aqueous hydrocotrisone enemas (Cortenemas) or a suspension of hydrocortisone in an inert foam base (Colifoam). Each treatment contained the same amount of hydrocortisone. Clinical, sigmoidoscopic, and histological response was assessed after two weeks. Both agents were effective, and broadly similar in terms of objective improvement, but subjective improvement was greater with the foam preparation, and several patients expressed a preference to this mode of treatment.